Evaluasi Kesuksesan Sistem Informasi Absensi Online Menggunakan Model Delone MCLEAN - Ratna Kartika Wiyanti; Ni Luh Ayu Kartika Yuniastari Sarja (Media Aplikom, 2018)
Information systems become one of the benefits of the organization. In supporting the academic process, STIKOM Bali utilizes Online Attendance Information System that is used to process the attendance of lecturing activities. The success of a company's information system depends on how the system is run, the ease of the system for its users, and the utilization of the technology used. One of the most important goals in evaluating the application of information systems is knowing the success rate of the information system. Measuring the success of Online Attendance Information System has not been done so that not yet known success or failure of the system. Therefore it is necessary to evaluate the success of this system. This study evaluates the success of using the Delone Mclean model. The research method used in this research is problem definition, concept exploration and observation, analysis, data collection and analysis and conclusion. Based on the results of hypothesis testing with correlation method found that there are six proven hypotheses so it can be concluded that online attendance information system has been successfully applied to STIKOM Bali. Keywords: online attendance information system, evaluation of success, delone mclean model, correlation